Endothelial capture using antibodies and nanoparticles in human tissues: antigen identification and liver segment imaging - Wang, Zhe; Gross, Wolfgang; Mehrabi, Arianeb; Ryschich, Eduard (Acta biomaterialia, 2019)
Background: The unique phenomenon of endothelial antibody capture (endocapt) leads to site-specific accumulation of antibodies on the endothelium after its locoregional injection. The potential of this phenomenon has already been demonstrated in animal models. In the present study, the translational potential of several human endothelium-specific antibodies for their use in the endocapt-based approach was analysed. Methods: The binding of different endothelium-surface specific monoclonal antibody clones was analysed in human tissue and in endothelial cells using image-based immunofluorescence and the determination of half-maximal effective concentration (EC50). The potential of endocapt-based locoregional application of antibodies or antibody-coated liposomes was analysed ex vivo using isolated mouse liver perfusion and in vivo using superselective injection in tumour models. Results: Eight out of ten antibody clones were assigned to the group of “fast binding antibodies”. Different antibody clones showed various binding kinetics to the same endothelial marker whereas the binding kinetics of single antibody clones was independent from the tissue type. Anti-CD49e, anti-CD31, anti-CD34 and anti-CD102 antibodies showed the lowest EC50 of antibody binding concentration and constant results in EC50 determination of antibody binding to cells and human tissue. Experimental studies using anti-mouse CD49e antibody and coated immunoliposomes confirmed their effective capture by endothelial cells in vitro and in vivo by which fluorescent liver segment labelling was achieved. Conclusions: Our findings identify the high potential of several human antibody clones, especially anti-CD49e, -CD31, -CD34 and -CD102, for endocapt technology. We also propose important translational implications of these antibodies for image-guided liver surgery and for use of nanoparticles/immunoliposomes. Toxicological studies are indispensable for further translational development of new antibodies for endocapt. - Statement of Significance - The phenomenon of endothelial antibody capture (endocapt) leads to site-specific accumulation of antibodies on the endothelium after its locoregional injection. This phenomenon broadly prevents systemic circulation of the antibody or antibody-drug conjugates. In the present study, our findings identify several human antibody clones promising for endothelial capture technology. This study provided the experimental demonstration of liver segment labelling ex vivo using isolated mouse liver perfusion and in vivo using superselective injection in tumor models. In addition, this study proposed the important translational implications of selected antibodies for image-guided liver surgery and for use of nanoparticles/immunoliposomes.
Gesehen am 13.03.2020